Recycling versus Long-Term Storage of Nuclear Fuel: Economic Factors - B. Yolanda Moratilla Soria; Maria Uris Mas; Mathilde Estadieu; Ainhoa Villar Lejarreta; David Echevarria-López (Science and Technology of Nuclear Installations)
The objective of the present study is to compare the associated costs of long-term storage of spent nuclear fuel—open cycle strategy—with the associated cost of reprocessing and recycling strategy of spent fuel—closed cycle strategy—based on the current international studies. The analysis presents cost trends for both strategies. Also, to point out the fact that the total cost of spent nuclear fuel management (open cycle) is impossible to establish at present, while the related costs of the closed cycle are stable and known, averting uncertainties.